The natural diversity and ecology of fission yeast. Issue 3 (8th February 2018) - Jeffares, Daniel C.
Abstract: While the fission yeast is a powerful model of eukaryote biology, there have been few studies of quantitative genetics, phenotypic or genetic diversity. Here I survey the small collection of fission yeast diversity research. I discuss what we can infer about the ecology and origins of Schizosaccharomyces pombe from microbiology field studies and the few strains that have been collected. Abstract : Fission yeast has been intensively study in the laboratory ‐ but we know very little about its life in natural environments. Of course, it must have had a natural origin somewhere. Here I discuss what we know about wild fission yeasts; their genetics, genomics and the little we know about their natural environments.